MANAJEMEN PEMBERDAYAAN MASYARAKAT SENTRA KOPI DI DESA WISATA DOESOEN SIRAP KABUPATEN SEMARANG - Atika Putri Rahayu; Dewi Rostyaningsih; Hesti Lestari (Journal of Public Policy and Management Review, 2022)
Dusun Sirap is located in Jambu District, Semarang Regency, has a lot of potential in its natural resources, especially in the fields of plantations and coffee farming. Recently, coffee has become a promising commodity to be developed due to the proliferation of cafes in Indonesia. The existing phenomenon has not been able to prosper the community at large. Unfortunately, Dusun Sirap is still facing problems in maximizing the management of community empowerment programs carried out in the area. The community empowerment program can be carried out optimally if it is carried out with the right methods, such as by looking for stages of community empowerment that are in accordance with the conditions of the community and the hamlet area. The research method used is descriptive qualitative. The author uses data collection techniques through interviews, observation, and documentation. The author determines the subject using a snowball sampling technique, the quality of the data using a source triangulation model. The author got the results of research which showed that in order to be able to manage community empowerment programs that produce the best output, Dusun Sirap can carry out 4 stages of community empowerment, namely, 1) Preparation Stages, 2) Assessment Stages, 3) Alternative Planning Stages of Activities or Programs, 4) Stages Implementation of Empowerment Activities. Supporting factors for community empowerment in Dusun Sirap include, 1) The location is rich in abundant natural resources, 2) The community has a passion for developing their territory, 3) Facilities from related agencies and the private sector (BCA). The inhibiting factors are, 1) The community does not have sufficient insight and knowledge, 2) The government has not paid attention to the tourism potential of Sirap Hamlet, 3) Limited access roads and fleet facilities. The author provides suggestions such as, a) The community needs to improve their capabilities in the field of technology, b) Officers must find the right solution to overcome the problem of plantation plant pests, c) Empowerment officers need to find solutions from the presence of steep paths or access roads, d) The government needs to pay more attention to the tourism sector, e) Steep and narrow road access can be improved by utilizing local residents' land as parking locations and providing sufficient fleets, f) Community empowerment actors sell products through an online system by utilizing marketplace platforms such as Tokopedia, Shopee, Lazada, etc.